PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 008 REJOSARI KECAMATAN LIRIK KABUPATEN INDRAGIRI HULU - Mardiana Mardiana; Otang Kurniaman; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack : This research at performs since its low usufruct IPS'S studying III. class student SDN 008 Rejosari that haven't reached KKM (Minimum thoroughness criterion) one that is established which is 65. This appears from peneletian's startup data of 13 students which reach points according to KKM as much 6 students (46%), meanwhile student that haven't reached KKM'S point as much 7 students (54%). Base about problem research do that action brazes with learnings model implement Numbered Head Together (NHT) one that intent to increase IPS'S studying result III. class student SDN 008 Rejosari School Years 2014 / 2015. This research is executed deep two cycles, whereabouts on each cycle it consisting of two-time appointment gazes to show face and once daily dry run. With be applied Model Learning Numbered Head Together (NHT), therefore gets to increase IPS'S studying result III. class student SD Country 008 Rejosari on kehiatan's material merchant and money and its utility. It can at see of acquired studying result student on base score which is with thoroughness percentage 46%, with average 61,15, worked up on i. cycle with thoroughness percentage 69,23% by average 67,3. Worked up again on cycle II.which is with thoroughness percentage 92,3% by average 77,3. On Activity learns first cycle with percentage average 70,83% worked up as 89,58% on second cycle. Student activity on first cycle with percentage average 74,99% worked up as 87,5% on second cycle. Of acquired data as above as gets to be known that pass through learning model Implement Numbered Head Together(NHT) can increase IPS'S studying result III. class student SDN 008 Rejosari.Key word: Numbered Head Together, IPS'S Learned result